SSR-based evaluation of genetic diversity in populations of Agriophyllum squarrosum L. and Agriophyllum minus Fisch. & Mey. collected in South-East Kazakhstan - Y. Genievskaya; D. Karelova; S. Abugalieva; P. Zhao; G. Chen; Y. Turuspekov (Вавиловский журнал генетики и селекции)
The development of informative polymorphic DNA markers for poorly studied genera is an important step in population analyses of living organisms, including those that play very important ecological roles in harsh environments, such as desert and semi-desert area. Examples of those poorly studied desert species are Agriophyllum squarrosum L. and Agriophyllum minus Fisch. & Mey. However, a recent RNA-sequencing project in A. squarrosum has proposed a large set of hypothetical SSR (simple sequence repeat) markers. In this work, 11 novel polymorphic SSRs were found due to the screening of 24 randomly selected SSRs for three populations of A. squarrosum and one population of A. minus. The analysis of 11 SSRs revealed 16 polymorphic loci in two Agriophyllum species, 8 polymorphic loci within three populations of A. squarrosum, and 6 polymorphic loci in the population of A. minus. Statistical analyses showed high interspecific, but relatively low intraspecific genetic diversity. The phylogenetic clusterization and population structure analysis have demonstrated a clear segregation of A. minus from A. squarrosum, as well as the separation of population 1 from populations 2 and 3 of A. squarrosum. Thus, we identified the set of novel and informative SSR markers suitable for the study of genetic diversity in Agriophyllum.